Zooplankton distribution in a marine protected area: the Berlengas Natural Reserve (Western Coast of Portugal) - Mendes, Susana (2020)
Zooplankton distribution in the Berlengas Natural Reserve (Portugal) was studied over a period of one year (February 2006 to February 2007). Monthly sampling was performed at 6 stations, differentiated according to depth and distance to the coastline. The aim of this study was to investigate the overall zooplankton variability through its different dimensions (space vs. time). The Partial Triadic Analysis (PTA) was used to study the spatial variability of the zooplankton community and its dynamics in time and the dynamic trajectories of the zooplankton species for each site. It was possible to distinguish a neritic-ocean gradient of the zooplankton composition and a temporal variability. Four distinct periods can be highlighted considering the distribution of the dates and the arrangement of the species: (i) the first one comprised August to November, (ii) the second one was related to June and July, (iii) the third one associated with spring (April and May) and, (iv) the latest one was related to winter (February, March and December 2006 and January and February 2007). The PTA method showed the similarities between the successive data tables and proved to be useful for investigating biotic structures and detecting spatial-temporal patterns in zooplankton distribution.